Relationship between the national universities commission resource allocation parameters used in allocating funds to teaching and learning and research and development and the outcomes of federal universities in Nigeria - Bello Garba, Kofar Sauri (2018)
The National Universities Commission Resource Allocation Parameters were developed by the National Universities Commission (NUC), for the allocation of funds to all the federal universities in Nigeria. However, the outcomes of the universities in their core tasks of teaching and research have left much to be desired, considering the volume of funds allocated to them annually. The funding parameters were described as input driven and does not therefore consider the outcomes of the federal universities, especially in their core tasks of teaching and research. The basic aim of this study, therefore, was to examine the relationship between the NUC funding parameters with the outcomes of the federal universities in Nigeria. A mixed mode design was adopted by the study where qualitative data was first collected, analyzed and then, together with relevant literatures, used to develop a survey instrument for the quantitative phase of the study. The study surveyed 209 senior management staff of the federal universities in Nigeria, and the results were analyzed using the IBM SPSS for Windows and SEM-PLS3. Factor analysis was conducted to identify the number of factors for the study, from where the measurement and structural models were built to identify the relationship between the funding parameters and the outcomes of the federal universities. The findings revealed that there is a positive and a statistically significant relationship between academic support, academic facilities and academic research with the teaching outcomes of the federal universities, while only academic support and academic facilities showed a similar relationship with research outcomes. The study has thus been able to fill the knowledge gaps that exists in the relationship between the funding parameters used in allocating funds to teaching and research with the outcomes of the federal universities in Nigeria.